Knowledge and Attitude Students Through Nutrition Health Education with E-Modul “Against Stunting” - Adriyani Adam; Aswita Amir; Dinul Islam; Ali Imran (GLOBAL HEALTH SCIENCE GROUP, 2022)
Stunting in Indonesia is a very serious problem because the percentage is above form cut off point of World Health Organization is only 20%. The results of South East Asia Nutritions Surveys (SEANUTS), around 24.1% of boys and 24.3% of girls in Indonesia are stunted. Based on Basic Health Research (2018), the incidence of stunting among children under five in South Sulawesi is still high, which is above 30% and South Sulawesi is the fourth highest in Indonesia. One of the preventive efforts to reduce stunting from an early age by nutrition health education through developing an electronic module about stunting as a method of nutrition health education which contains information about stunting. The purpose of this study was to determine the effect of nutrion health education on students' knowledge and attitudes through the development of the E-Module